EVALUASI USER INTERFACE PADA APLIKASI E-COMMERCE (STUDI KASUS INFORMA DAN IKEA) - Ilkham, Sundari; Kusrini, Kusrini; Arief, M. Rudyanto (Informasi Interaktif, 2019)
ABSTRACT Increasingly complex human needs cause changes in the community environment. This is indicated by the increasingly rapid development of information technology, especially information technology related to online shopping applications through e-commerce applications. The development of technology that is currently being talked about and is the subject of discussion is to develop technology towards modern business by using mobile-based e-commerce applications. Anywhere and anytime quickly and in real time, people can easily make purchases of any product related to the needs of the house they are looking for. The results of this study were to determine the magnitude of the heuristic value of the quality of the mobile e-commerce application user interface Informa and Ikea according to users using the Nielsen 10 principle method. It is expected that the results of this study can be used as input for e-commerce mobile application developers Informa and Ikea to be better, and can be proposed to improve the user interface for e-commerce applications Informa and Ikea. Keywords:  E-Commerce, User Interface, 10 Nielsen Principles.